Making safety training stickier: A richer model of safety training engagement and transfer. (September 2021) - Casey, Tristan; Turner, Nick; Hu, Xiaowen; Bancroft, Kym
Graphical abstract: Highlights: An integrated model of safety training engagement and transfer is developed. Pre-training, training delivery and design factors increase engagement. Engagement leads to learning and higher rates of safety training transfer. Practical recommendations for the design, delivery, and sustainability of safety training are given. Abstract: Introduction: Compared to other types of occupational training, safety training suffers from several unique challenges that potentially impair the engagement of learners and their subsequent application or "transfer" of knowledge and skills upon returning to the job. However, existing research on safety training tends to focus on specific factors in isolation, such as design features and social support. The aim of this research is to develop an overarching theoretical framework that integrates factors contributing to training engagement and transfer. Method: We conducted a comprehensive qualitative review of safety training research that was published between 2010 and 2020. We searched Web of Science, Scopus, and Google Scholar, yielding 147 articles, and 38 were included. We content analyzed article summaries to arrive at core themes and combined them with contemporary models of general occupational training to develop a rich model of safety training engagement and transfer. Results: We propose that training engagement is a combination of pre-training factors such as individual, organizational, and contextual factors, that interact with design and delivery factors. Safety training engagement is conceptualized as a three-component psychological state: affective, cognitive, and behavioral. Organizations should prioritize pre-training readiness modules to address existing attitudes and beliefs, optimize the safety training transfer climate, and critically reflect on their strategy to design and deliver safety training so that engagement is maximized. Conclusions: There are practical factors that organizations can use before training (e.g., tailoring training to employees' characteristics), during training (e.g., ensuring trainer credibility and use of adult learning principles), and after training (e.g., integrating learned concepts into systems). Practical Applications: For safety training to 'stick, ' workers should be affectively, cognitively, and behaviorally engaged in learning, which will result in new knowledge and skills, improvements in attitudes, and new safety behaviors in the workplace. To enable engagement, practitioners must apply adult learning principles, make the training relevant, and tailor the training to the job and individual needs. After training, ensure concepts are embedded and aligned with existing systems and routines to promote transfer.